Analysis of the Role of the Marine Corps Task Force for the Security of the Eastern Outer Islands in the Context of Maintaining the Sovereignty of the Republic of Indonesia - Alimin, Alimin (STKIP Yapis Dompu, 2022)
Indonesia has border areas with many countries, both land (Continent) and sea (Maritime) borders. On December 13, 1957, the Indonesian government, which was then led by Ir. Djuanda issued a government announcement known as the Djuanda Declaration. This declaration states that the Republic of Indonesia is an archipelagic state. This study was designed using a qualitative approach. This qualitative research is research conducted in natural conditions (not allowed to change or manipulate the background or research construction) which prioritizes the process rather than the results, is more descriptive and performs inductive data analysis. Based on the results of a comparative analysis of conceptual models on regulations regarding the role of the Marine Task Force in the role of the Marine Task Force in securing the Eastern Outer Islands in safeguarding the sovereignty of the Republic of Indonesia, it was found that there is a range between the real world and system thinking (gap) where the activities have not been carried out (research gap) by related instruments. Furthermore, a discussion of the research gap is carried out and analyzed using theory, previous research and the results of research interviews.